Attitudes of spouses towards abortion and the quality of their mutual relations - Rawicka, Iwona (Kwartalnik Naukowy Fides et Ratio, 2022)
In recent years there have been a lot of social and political discussions concerning legal aspects of abortion in Poland and lessening restrictions in this area. Nevertheless there are few debates on social, psychological and medical effects for women and men who take the decision of abortion both on individual basis and in their mutual relationship. In the article the research has been conducted concerning relation between women’s and men’s attitudes towards abortion and the quality of their marital relationship. It cannot be explicitly stated what results abortion can bring in their common relationship. However, it can be estimated to what extend the cognitive, emotional and motivational aspect of their attitude towards abortion is connected with the quality of their marital bonding, love, communication and the feeling of being well-matched. In the research the method of diagnostic survey was used. To collect data estimating the quality of marriage the following four standardized exploratory tools were applied: Marital Bonding Scale of Józef Szopiński, Love Measure Questionnaire according to Robert Sternberg, adopted by Bogdana Wojciszke, Marital Communication Questionnaire by Maria Kaźmierczak and Mieczysław Plopa, and Marital Match Questionnaire by Jan Rostowski and Mieczysław Plopa. In order to estimate the respondents’ attitude towards abortion the researchers used one of the statements from the scale of attitude towards parenthood by Marta Komorowska-Pudło. On the basis of the data collected in the research it can be diagnosed that the attitudes of a married couple towards abortion have a statistically significant association with their mutual relationship, however not a big one. The higher level of acceptance they expressed  for the abortion in the situation of an unplanned pregnancy ,the lower was the level of the satisfaction in their marital bonding, love, communication and feeling of being well-matched.  At the same time with the increase of their level of satisfaction in their mutual relationship, their negative attitude towards abortion as a birth control tool was also growing. On the basis of comparison of the research results with data presented in the literature regarding the quality of married couples who had abortion, one can conclude that the attitude of married couples towards abortion in reference  to cognitive and emotional-motivational components  are connected in a similar way with the quality of their relationship, as in case of the attitude of married couple towards abortion in behavioral  component aspect. Accepting abortion (pro-choice attitude) is connected with less satisfactory relationships between men and women in marriages. On the other hand the lack of acceptance of abortion (pro-life attitude) results in the higher level of the quality of their relationship.